2016
DOI: 10.1128/jb.00077-16
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Coenzyme A Biosynthesis in the Hyperthermophilic Bacterium Thermotoga maritima

Abstract: Regulation of coenzyme A (CoA) biosynthesis in bacteria and eukaryotes occurs through feedback inhibition targeting type I and type II pantothenate kinase (PanK), respectively. In contrast, the activity of type III PanK is not affected by CoA. As the hyperthermophilic bacterium Thermotoga maritima harbors only a single type III PanK (Tm-PanK), here we examined the mechanisms that regulate CoA biosynthesis in this organism. We first examined the enzyme responsible for the ketopantoate reductase (KPR) reaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The use of the archaeal rather than the bacterial reaction order for the synthesis of the CoA intermediate d -4′-phosphopantothenate in the symbiotic Entoporibacteria group mirrors what has been shown in the archaea Picrophilus torridus , in which an enzyme much closer to the bacterial PanK than to the canonical archaeal PoK was found and has been annotated as “archaeal PanK” ( Takagi et al. 2010 ; Shimosaka et al. 2016 ).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The use of the archaeal rather than the bacterial reaction order for the synthesis of the CoA intermediate d -4′-phosphopantothenate in the symbiotic Entoporibacteria group mirrors what has been shown in the archaea Picrophilus torridus , in which an enzyme much closer to the bacterial PanK than to the canonical archaeal PoK was found and has been annotated as “archaeal PanK” ( Takagi et al. 2010 ; Shimosaka et al. 2016 ).…”
Section: Resultsmentioning
confidence: 59%
“…However, in the two bacteria Corynebacterium glutamicum and Thermotoga maritima that also lack a classical KPR, it has been demonstrated that this activity is performed by the ketol-acid reductoisomerase (KARI) encoded by the ilvC gene, an enzyme classically involved in the biosynthesis of branched-chain amino acids ( Merkamm et al. 2003 ; Shimosaka et al. 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Loss of ilvC causes pantothenate auxotrophy in Corynebacterium glutamicum, a close relative of Mtb 35 , and IlvC is the only KPR in Thermotoga maritima 36 . These observations demonstrate that IlvC is the only protein with KPR activity in some bacteria.…”
Section: Metabolomicsmentioning
confidence: 99%
“…Other unique biochemical traits of PanKIII include the requirement for a monovalent cation such as NH4 + or K + [31], and no appreciable affinity for pantothenamides [30]. TmPanKIII was reported to experience negative CoA feedback, with complete inhibition at about 400 µM of CoA [41], whereas Helicobacter pylori PanKIII and Bacillus subtilis PanKIII are not affected by CoA or its thioesters [30], suggesting heterogeneity in regulation within PanK types. PanKIII isoforms can be found across almost all phyla of bacteria [9], and typically have a high KM for ATP (PanKIII KM: B. anthracis = 510 µM [42], B. subtilis = 3.1 mM [30], H. pylori = 7.9-9.6 mM [30,40], T. maritima = 6.0 mM at 50 o C [9]), and little affinity for other phosphate donors [31].…”
Section: General Differences Between Panki Pankii and Pankiiimentioning
confidence: 99%